Association study of interleukin-19 rs2243188 polymorphism with systemic lupus erythematosus in a Chinese population. (September 2014) - Ni, Jing; Zhang, Min; Zhu, Yan; Chen, Gui-Mei; Liu, Juan; Zhang, Chao; Li, Lian-Ju; Pan, Hai-Feng; Ye, Dong-Qing
Abstract The purpose of this study was to evaluate whether a single-nucleotide polymorphism (SNP), rs2243188 of interleukin-19 (IL-19), show significant evidence for association with SLE in a Chinese population. A total of 545 SLE patients and 613 healthy controls were collected in the present study. The genotyping of IL-19 rs2243188 polymorphism was detected by TaqMan allele discrimination assay on the 7300 real time polymorphism chain reaction system. The minor C allele of rs2243188, relative to the major A allele, appeared to have a significantly lower frequency in SLE patients (31.0%) as compared with controls (35.5%) (χ2 = 5.19, p = 0.023). We also discovered a statistical significance in the dominant model (CC + CA versus AA: OR = 0.755, 95% CI = 0.598–0.953, p = 0.018). However, no significant difference in genotype distribution was found between SLE patients and controls (p = 0.056). Furthermore, an increased frequency of CC genotype were also detected in lupus nephritis (LN) groups as compared with non-LN groups (p = 0.024). Besides, the individuals with CC genotype had a 2.201-fold higher risk for the susceptibility to LN than those A allele carriers (AA + CA) (p = 0.006). Unfortunately, the analyses on the relationship of IL-19 rs2243188 with several clinical manifestations of SLE failed to find any significant results. In conclusion, our observations suggested the minor C allele of SNP rs2243188 might be a protective factor for SLE in a Chinese Han population. Moreover, the subgroup analysis highlighted that IL-19 rs2243188 SNP was associated with the susceptibility to LN patients.